IMPLEMENTASI BARCODE PADA SISTEM ABSENSI DAN PENGGAJIAN GURU BERBASIS WEB - Afin Maulana; Purnomo Hadi Susilo; Agus Setia Budi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The management of attendance and teacher payroll at TPQ Baitul Makmur Cumpleng was previously still carried out manually, causing the process of recording attendance, calculating salaries, and preparing reports to take a relatively long time and potentially cause recording and calculation errors. This research aims to implement barcode technology in a web-based teacher attendance and payroll system to improve the efficiency, accuracy, and effectiveness of administrative data management. The system development method used is the Waterfall method which includes needs analysis, system design, implementation, and testing. The system was developed using the CodeIgniter 4 Framework, PHP programming language, MySQL database, and barcode technology as a medium for teacher identification in the attendance process. Attendance data obtained through barcode scanning is automatically stored in the database and used as the basis for calculating salaries, allowances, and deductions in an integrated manner. System testing is carried out through the measurement of the level of process speed by comparing the completion time of administrative activities before and after using the system. The test results show that the system is able to speed up the attendance process, data processing, payroll calculation, and report creation compared to manual methods. In addition, the system is able to reduce recording errors, improve data accuracy, and produce more structured and accessible attendance and payroll information. Thus, the implementation of barcodes in the web-based attendance and payroll system is able to increase the effectiveness and efficiency of administrative management at TPQ Baitul Makmur Cumpleng.